Divided co-ownership and matrimonial property in legal regulations of Slovak Republic - Magdaléna Kerul'ová (Contemporary Economics, 2008)
The objective of the study is to transparently outline a system of relations connected with two different forms of property right that are incorporated in Slovak legal system. In this study author dealt with principles of the divided co-ownership and matrimonial property which lead to the pointing up to the differences between these legal concepts. On the basis of analysis of the null and present rules of law author persuade to the conclusions which are evaluation of the present status and inevitability of the changes in the future.
Keywords: 330